2019
DOI: 10.1016/j.impact.2018.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Development of a standardized food model for studying the impact of food matrix effects on the gastrointestinal fate and toxicity of ingested nanomaterials

Abstract: Food matrix effects impact the bioavailability and toxicity of pharmaceuticals, nutraceuticals, pesticides, and engineered nanomaterials (ENMs). However, there are currently no standardized food models to test the impact of food matrix effects using in vitro gastrointestinal models. The purpose of this study was to establish a standardized food model (SFM) for evaluating the toxicity and fate of ingested ENMs and then to assess its efficacy by examining the impact of food matrix effects on the toxicity of TiO2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
69
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(75 citation statements)
references
References 55 publications
5
69
0
1
Order By: Relevance
“…It has already been shown that certain ENMs have the capacity to alter the bioavailability of nutrients [59] while others may increase the bioavailability of noxious agents, like pesticides. [57] In addition, food matrix effects have been shown to modulate the bioactivity of ENMs, [32,35] and the gut microbiome and proteome of animals is known to be sensitive to the presence of chemically active particulates. [28,29,60] Therefore, we plan to apply the methods developed here to interrogate the physicochemical transformations, toxicological assessment, and effect on gut microbiome and proteome of GO in the presence of more complex food models.…”
Section: In Vitro Toxicological Assessment Of Small Intestinal Go Digmentioning
confidence: 99%
See 1 more Smart Citation
“…It has already been shown that certain ENMs have the capacity to alter the bioavailability of nutrients [59] while others may increase the bioavailability of noxious agents, like pesticides. [57] In addition, food matrix effects have been shown to modulate the bioactivity of ENMs, [32,35] and the gut microbiome and proteome of animals is known to be sensitive to the presence of chemically active particulates. [28,29,60] Therefore, we plan to apply the methods developed here to interrogate the physicochemical transformations, toxicological assessment, and effect on gut microbiome and proteome of GO in the presence of more complex food models.…”
Section: In Vitro Toxicological Assessment Of Small Intestinal Go Digmentioning
confidence: 99%
“…[30] Still, there are knowledge gaps regarding the toxicokinetics of ingested ENMs following absorption from the GIT, their acute and chronic effects on the gastrointestinal barrier, and their toxicodynamics, including biotransformations as they undergo digestion. Food matrix may further modulate the response of biological systems to ingested ENMs [31,32] and complicate the identification of physical and chemical alterations which might govern their toxicological impact. These alterations include biodissolution, [33] biomolecular corona formation, [34] and morphological changes, like agglomeration.…”
Section: Introductionmentioning
confidence: 99%
“…[38] Due to their high reactivity, NMs might interact with food components, such as carbohydrates, lipids, proteins, and minerals, which may influence their size, charge, agglomeration state, and surface composition. [35,37,39,40] Besides, once ingested, AgNPs pass through the GIT in which physiological parameters (e.g., pH, ionic strength, protein composition) are constantly evolving and thus influencing the features of AgNPs throughout the digestion process. [38,41,42] As toxic effects of NMs are related to their physicochemical properties, [21,43] all the alterations that could take place before AgNPs attain the intestinal cells might affect their potential toxicity [35,39] and must therefore be included in cytotoxicity investigations to realize an accurate risk assessment.…”
Section: Introductionmentioning
confidence: 99%
“…[35,37,39,40] Besides, once ingested, AgNPs pass through the GIT in which physiological parameters (e.g., pH, ionic strength, protein composition) are constantly evolving and thus influencing the features of AgNPs throughout the digestion process. [38,41,42] As toxic effects of NMs are related to their physicochemical properties, [21,43] all the alterations that could take place before AgNPs attain the intestinal cells might affect their potential toxicity [35,39] and must therefore be included in cytotoxicity investigations to realize an accurate risk assessment. [37] The European Food Safety Authority (EFSA) has published a guidance in which recommendations were given for risk assessment of nanomaterials used in the food chain.…”
Section: Introductionmentioning
confidence: 99%
“…Marked reduction in toxicity was observed in tri‐culture epithelial cell models following exposure to E171 TiO 2 transformed through their interaction with a standard food model. [ 129 ] ENM speciation change was also noted to affect ENM induced toxicity, demonstrated by a reduction in observed ecotoxicity caused by the transformation of Ag ENMs to Ag 2 S. [ 6b,130 ] Therefore, Ag ENMs transformation to Ag 2 S and AgCl species occurring due to their gastric dissolution and interaction with macromolecules along the GIT could reduce intestinal toxicity. Notably, transformation of E171 TiO 2 have been noted to increase the bioavailability and, hence, toxicity of the pesticide, boscalid, in a small intestine tri‐culture model.…”
Section: Enm Translocation Across Git and Toxicological Outcomes In Gmentioning
confidence: 99%